Influence of climatic factors on spatio-temporal variabilities in the occurrence of aflatoxins in major food grains available at retail shops in Bangladesh - Neogi, Sucharit Basu; Uddin, Md Nasir; Arif, Mohammad; Sen, Ashis Ratan; Paul, Priyanka Rani; Saddam, Md Jahidul Islam; Haque, AKM Ziaul; Samosornsuk, Seksun; Samosornsuk, Worada; Kabir, S M Lutful (Asian-Australasian Journal of Food Safety and Security, 2024)
In Bangladesh, little is known about the role of climatic factors influencing spatio-temporal occurrence among different food grains of aflatoxins, which have been linked to liver cancer cases and other health hazards. In this study, 252 food grain samples of 10 types were collected from retail markets at 18 districts, pre-monsoon, monsoon and post-monsoon seasons during February-September, 2018. Occurrence and concentration of total aflatoxins in the samples were analysed by a direct competitive enzyme-linked immunosorbent assay, and compared with climatic data (temperature, humidity, rainfall, and sunshine hours). Contamination of aflatoxins was found in approx. 38% (n=96) of the total samples, with highest occurrence in groundnuts (82%), followed by corn grains (70%), chick pea (54.5%), wheat grain (50%) and green gram (42.9%). Aflatoxins occurrence was moderate in split chick pea (30.8%), yellow pea (28.2%), black gram (27.8%), and lentils (27.6%), while the lowest in grass pea (17.6%). Aflatoxins concentration was found to exceed the European Union permissible limit (≤5 µg kg-1) in 33 (13.1%) samples. Overall, approximately 5.6%, 7.5%, and 25.0% samples were contaminated with high (10-19 ppb), medium (5-9 ppb) and low (1-4 ppb) concentrations of aflatoxins, respectively. High level concentration of aflatoxins was more frequent in groundnut (36%) and wheat grain (20%), in comparison to other types. Occurrence of aflatoxins during pre-monsoon was detected among 21% (19/91) samples, which increased to ca. 30% (36/119) during monsoon, and 98% (41/42) during post-monsoon. However, aflatoxins mean concentration during post-monsoon was comparatively low than the other seasons. Variations in aflatoxins monthly prevalence correlated significantly with relative humidity (p ≤ 0.01) and rainfall (p≤ 0.05), when a 1-month time lag was considered. Therefore, predisposing climatic conditions, i.e., rainfall incidences and persistence of higher relative humidity in the previous month(s), have salient influence on aflatoxins occurrence, potentially impacting both pre-harvest and stored food grains. This study underscores the need of a more holistic monitoring of aflatoxins in agricultural products for a longer term, and adoption of proper intervention measures for food grains while being stored and before consumption. Asian Australas. J. Food Saf. Secur. 2024, 8(2), 32-47